2021
DOI: 10.1038/s41467-021-23663-2
|View full text |Cite
|
Sign up to set email alerts
|

A deep learning approach to identify gene targets of a therapeutic for human splicing disorders

Abstract: Pre-mRNA splicing is a key controller of human gene expression. Disturbances in splicing due to mutation lead to dysregulated protein expression and contribute to a substantial fraction of human disease. Several classes of splicing modulator compounds (SMCs) have been recently identified and establish that pre-mRNA splicing represents a target for therapy. We describe herein the identification of BPN-15477, a SMC that restores correct splicing of ELP1 exon 20. Using transcriptome sequencing from treated fibrob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 93 publications
(127 reference statements)
0
35
0
Order By: Relevance
“…Training datasets are trained under the traditional CFAR [12], BPNN [15], Faster R-CNN [16], SSD512 [17], and CFAR-DBN algorithms. After the corresponding training model is obtained, the test dataset is tested under the above five algorithms.…”
Section: Sar Image Detection Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Training datasets are trained under the traditional CFAR [12], BPNN [15], Faster R-CNN [16], SSD512 [17], and CFAR-DBN algorithms. After the corresponding training model is obtained, the test dataset is tested under the above five algorithms.…”
Section: Sar Image Detection Resultsmentioning
confidence: 99%
“…As a hot technology with rapid development in the field of artificial intelligence in recent years, deep learning has been widely used in various industries. Deep learning comprehensively learns the abstract information from low level to high level through nonlinear elements [15][16][17], which reduces the complex preprocessing in the early stage of artificial intelligence and improves the efficiency of target detection and recognition. At present, the research on ship target detection in SAR images based on depth learning has become a hot topic in the application of related fields.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported DL for therapeutic target prediction in recent years [175][176][177]. For example, Wang et al [178] constructed a framework that combines a biased support vector machine and a stacked auto-encoder DL model to identify drug target proteins.…”
Section: Review and Prospection Of Deep Learning Architecture In Target Identificationmentioning
confidence: 99%
“…Six associated pathways were over-represented in all 6 disorders, including the major and the minor mRNA splicing pathways and RNA metabolism. Therefore, we found that aberrations in the mRNA splicing process may be a common trajectory to many complex brain disorders involving the spliceosome complex.Recently, AS dysregulation was reported in AD, where several mis-splicing events in the brain have been associated with amyloid burden and neuro brillary [21], ASD, SCZ [28][29][30][31], and Huntington's disease [32,33], furthermore, emerging splicing therapeutics are promising therapeutic approaches in aberrant/deregulated AS [34][35][36][37][38], and clinical trials are currently underway for spinal muscular atrophy (https://clinicaltrials.gov/ct2/show/NCT04240314).We hypothesize that the excessive splicing changes observed in brain conditions may be related to changes in their regulators, spliceosome-related genes (SGs). Therefore, this study aims at identifying SG expression changes in multiple brain disorders using postmortem brain transcriptome data.…”
mentioning
confidence: 99%
“…Recently, AS dysregulation was reported in AD, where several mis-splicing events in the brain have been associated with amyloid burden and neuro brillary [21], ASD, SCZ [28][29][30][31], and Huntington's disease [32,33], furthermore, emerging splicing therapeutics are promising therapeutic approaches in aberrant/deregulated AS [34][35][36][37][38], and clinical trials are currently underway for spinal muscular atrophy (https://clinicaltrials.gov/ct2/show/NCT04240314).…”
mentioning
confidence: 99%